Net-Zero energy strategies for tropical hotels using passive design and PCM-Based envelope systems (ARTEKS : Jurnal Teknik Arsitektur, 2026)
Motivated by the advancement of the net-zero hospitality concept in Indonesia, and considering the relatively high average humidity levels found in tropical countries with varied climatic conditions, this study examines the effects of integrating phase change materials (PCMs) into hotel building envelope systems across six Indonesian cities representing a wide range of tropical climate classifications (Af, Am, Aw, and Bsh). The objective is to improve total energy consumption (TEC), life cycle cost (LCC), and carbon dioxide (CO?) emissions performance. This research evaluates the efficiency of PCM-reinforced wall systems under two dual-objective optimization scenarios: (1) TEC versus LCC and (2) TEC versus CO? emissions, using an integrated simulation framework combining DesignBuilder, EnergyPlus, and a multi-objective genetic algorithm (NSGA-II). The results indicate that PCM integration can substantially enhance total energy savings and reduce CO? emissions by up to 47.80 percent and 52.96 percent, respectively, particularly in earth-based and masonry wall assemblies. Significant economic benefits were also identified, with life cycle cost savings reaching up to 29.62 percent and reductions in the average tariff cost per square meter of approximately 22.15 percent in high-tariff zones, such as Denpasar, when these construction systems are applied. The optimal PCM configurations were found to be climate-dependent, performing most effectively with external PCM placement and melting temperature ranges between 23 and 29°C. Overall, the findings demonstrate that PCM integration can provide sustainable, cost-effective, and climate-responsive building envelope solutions for the hospitality sector in tropical regions. Furthermore, the study presents a robust optimization framework that is scalable for both retrofit applications and new construction, supporting Indonesia’s ecotourism development and zero-emission building agenda.
Keywords: LCC; Net-Zero hotels; Optimization; Passive design; PCM; Tropical climate